2015
DOI: 10.18232/alhe.v22i3.654
|View full text |Cite
|
Sign up to set email alerts
|

La fiabilidad en la distribución geográfica de las exportaciones argentinas, 1875-1913

Abstract: ** Resumen. El desempeño de la exportación en América Latina durante la primera globalización ha sido un tema muy estudiado en la historiografía. Sin embargo, la calidad de las fuentes de información para su análisis no ha sido tratada con la misma profundidad. En los últimos años han proliferado debates acerca de la fiabilidad de las estadísticas para conocer el crecimiento, la composición y la distribución geográfica del comercio exterior de la región. En este artículo proponemos confrontar los resultados de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 12 publications
0
4
0
1
Order By: Relevance
“…Authors such as Carreras-Marín and Badia-Miró (2008) 4 , validate the use of this source and point out its superior quality owing to a better geographical assignment. Other authors have deeply analysed and validated specific countries’ statistics, such as Argentina (Tena-Junguito and Willebald 2013; Carreras-Marín and Rayes 2015), Uruguay (Bonino-Gayoso et al . 2015) and Brazil (Absell and Tena-Junguito 2016).…”
Section: Accuracy Of Figures On Chilean Bilateral Trade With Its Mainmentioning
confidence: 99%
“…Authors such as Carreras-Marín and Badia-Miró (2008) 4 , validate the use of this source and point out its superior quality owing to a better geographical assignment. Other authors have deeply analysed and validated specific countries’ statistics, such as Argentina (Tena-Junguito and Willebald 2013; Carreras-Marín and Rayes 2015), Uruguay (Bonino-Gayoso et al . 2015) and Brazil (Absell and Tena-Junguito 2016).…”
Section: Accuracy Of Figures On Chilean Bilateral Trade With Its Mainmentioning
confidence: 99%
“…In fact, the results of this last exercise confirmed that Argentina’s import records were better than its export records, which was to be expected given the relevance of the imports in the Argentine tax scheme of the time. Tena-Junguito and Willebald (2013) and Carreras-Marín and Rayes (2015) have compared Argentine official export records with the import records of its main trade partners (the United Kingdom, Germany, France and Belgium, and the United Kingdom, Germany, France, Belgium, Spain, Italy, Brazil and the United States, respectively). The results of both exercises proved that the ADGEN tended to undervalue exports.…”
Section: The Official Trade Statistics In Argentina and The Accuracy mentioning
confidence: 99%
“…Para llevar adelante esta indagación acotada se tomaron los testimonios registrados por dos funcionarios del gobierno provincial que actuaron como inspectores y del perito alemán Kaerger, encargado por su gobierno de estudiar la expansión del trigo en Argentina. Los años de los respectivos informes fueron 1896 (Kaerger, 2004), 1898-1899 (Río, 1899) y 1906-1907(Aguilar, 1907. levantadas en mayo de 1895, dan cuenta de 3 189 unidades de la misma herramienta.…”
Section: Sobre Las Tierras De Marcos Juárezunclassified